Takotsubo cardiomyopathy in COVID-19: a case report. Haemodynamic and therapeutic considerations. Issue Volume 4:Issue FI1(2020)Special Issue (27th August 2020) - van Osch, Dirk; Asselbergs, Folkert W; Teske, Arco J
Abstract: Background: Cardiovascular complications are increasingly recognized during the current coronavirus disease 2019 (COVID-19) pandemic. Myocardial injury is most commonly described and its underlying mechanism is believed to be multifactorial. Next to Type 2 ischaemia, COVID-19 may lead to (peri)myocarditis or Takotsubo (or stress) cardiomyopathy. Case summary: A 72-year-old woman was admitted to the intensive care unit for mechanical ventilation because of respiratory insufficiency secondary to COVID-19 viral pneumonia. Seven days after admission, she developed new negative T-waves and a prolonged QTc interval on electrocardiography (ECG). Troponin levels were mildly elevated. Echocardiography showed a poor left ventricular systolic function with apical ballooning consistent with the diagnosis Takotsubo cardiomyopathy. Seven days afterwards, the ECG and troponin levels normalized. Echocardiography showed improvement of left ventricular systolic function, however with persistent hypokinesia of the apical segments. Coronary artery disease was excluded using coronary computed tomography angiography. The patient was discharged home and follow-up echocardiography after 3 months showed normal contractility of the apical myocardial segments, with normalization of the left ventricular systolic function, as expected in Takotsubo cardiomyopathy. Discussion: COVID-19 caregivers should be aware of Takotsubo cardiomyopathy as complication of COVID-19, since regular use of QT-prolonging drugs combined with prolongation of the QTc interval in Takotsubo cardiomyopathy may lead to life-threatening arrhythmias. Furthermore, Takotsubo cardiomyopathy may lead to acute heart failure and even cardiogenic shock. Frequent ECG monitoring of COVID-19 patients therefore is of paramount importance and timely echocardiography should be obtained when ECG abnormalities or haemodynamical problems occur.